TEKNOLOGI PENGOLAHAN SAMPAH DAN AIR LIMBAH - Herlambang, Arie; Martono, Djoko Heru (Center for Environmental Technology, 2008)
Solid waste has become a problem for large and small cities, as they relate to environmental sanitation and health, as well as aesthetic issues. High intensity of rainfall influenceÃ‚Â in a high solubility results of decomposition of waste in both TPS and TPA, brought the flow of water and water soak to soil or water flow to the public drainage. Law Number 8 Year 2007 on waste management require sanitary landfill technology. Currently most of the TPA are still not meet the full construction of sanitary landfill and need to be supported by the application of the 3R (Reduced, Reused, Recycle) program in solidwaste. ProcessingÃ‚Â waste liquidÃ‚Â derived from the leachate (seepage water) waste requiring special treatment. There are many type ofÃ‚Â waste water technology processing, the most important, It can be appliedÃ‚Â and product water quality meet the standard quality.Ã‚Â Keywords : Sampah, 3 R, Tempat Pembuagan Akhir (TPA), Leachate Treatment